Durability of eco-efficient binary cement mortars based on ichu ash: Effect on carbonation and chloride resistance. (August 2022) - Caneda-Martínez, Laura; Frías, Moisés; Sánchez, Javier; Rebolledo, Nuria; Flores, Elena; Medina, César
Abstract: This research work focuses on the performance of mortars containing ichu ash as a potential environmentally-sound alternative to traditional pozzolans (at 6% and 10% replacement levels) under CO2 and chloride ion rich environments, in order to evaluate the capacity of this material to produce more sustainable and durable blended cements. The results indicate that ichu ash increases the susceptibility to carbonation, although mortars with 6% ichu ash content behave similarly to OPC ones. However, both density and mechanical strength improve after 250 days of carbonation for both ichu-blended mortars. In terms of resistance to chloride penetration, the addition of ichu ash contributes to retaining the ions in the superficial layers of the mortars, inhibiting their advance. It was found that formulations with both 6% and 10% ichu ash content produced a reduction in the chloride diffusion coefficient of approximately 60%. This phenomenon was mainly attributed to the refinement and increased complexity of the microstructure of the mortars due to the pozzolanic effect. Therefore, it was found that in certain types of environments, ichu ash can be an interesting tool to improve the durability of cements while reducing their environmental footprint and exploiting local resources.